Numerical study of wind pressure on low-rise buildings induced by tornado-like flows. Issue 183 (December 2018) - Cao, Shuyang; Wang, Mengen; Cao, Jinxin
Abstract: This paper presents large-eddy simulation of tornado-induced pressures and forces on flat-roofed and gable-roofed low-rise buildings. The simulation is carried out with respect to an ISU-type tornado simulator and the simulation results are compared with available laboratory and field data. The present study shows that tornado-induced wind pressures have very different characteristics than those caused by boundary layer flows. The distribution and magnitude of wind pressures around the building models depend significantly on the distance between tornado vortex and building model. The roof angle does not alter the integrated wind loads on the gable-roofed building models significantly, but the local pressure on building surfaces, especially on the roof, depends obviously on the roof angle. However, this dependence is similar to that in boundary layer winds, although the value of the pressure coefficient is different due to pressure drop accompanying the tornado. In addition, the present study shows that the same horizontal profile of mean tangential velocity do not necessarily result in the same wind loads on building models in a tornado because of the difference in vortex structures. Highlights: Large-eddy simulation of tornado-induced wind loads on low-rise buildings is carried out. The simulation is carried out with respect to an ISU-type tornado simulator. The wind load depends on the three-dimensional flow structure. The pressure on building roof in tornadoes depends on the roof angle.